2014
DOI: 10.1126/scisignal.2004870
|View full text |Cite
|
Sign up to set email alerts
|

Memo Is a Copper-Dependent Redox Protein with an Essential Role in Migration and Metastasis

Abstract: Memo is an evolutionarily conserved protein with a critical role in cell motility. We found that Memo was required for migration and invasion of breast cancer cells in vitro and spontaneous lung metastasis from breast cancer cell xenografts in vivo. Biochemical assays revealed that Memo is a copper-dependent redox enzyme that promoted a more oxidized intracellular milieu and stimulated the production of reactive oxygen species (ROS) in cellular structures involved in migration. Memo was also required for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(149 citation statements)
references
References 49 publications
8
141
0
Order By: Relevance
“…Copper has emerged as an essential component of the metastatic process, and multiple preclinical studies have demonstrated that copper depletion decreases proliferation, blood vessel formation, tumor growth, and motility (11)(12)(13)(14)(15). Copper depletion may also reverse epithelial-mesenchymal transition (EMT) and downregulate expression of EMT-related genes, such as vimentin and fibronectin (16).…”
Section: Introductionmentioning
confidence: 99%
“…Copper has emerged as an essential component of the metastatic process, and multiple preclinical studies have demonstrated that copper depletion decreases proliferation, blood vessel formation, tumor growth, and motility (11)(12)(13)(14)(15). Copper depletion may also reverse epithelial-mesenchymal transition (EMT) and downregulate expression of EMT-related genes, such as vimentin and fibronectin (16).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity between the Memo1 ki/ki and F1-9-13FP mutant phenotypes further suggested that the ENU-induced mutation generated a null allele. We therefore assayed MEMO1 protein expression using a monoclonal antibody that recognizes the N-terminus of MEMO1 21 . Western blot analysis of protein isolated from E13.5 heads of either the F1-9-13FP mutants (Fig 3K) or Memo1 ki/ki mutants (Supplemental Fig 3) showed a complete absence of protein in both instances indicating that the ENU induced mutation likely generates a null allele.…”
Section: Resultsmentioning
confidence: 99%
“…Here we identify Memo1 , a gene that encodes a previously described receptor tyrosine kinase (RTK)-adapter molecule and reactive oxygen species (ROS) generating redox enzyme, as a novel effector in promoting bone ossification, most notably in the cranial base 21,22 . The importance of MEMO1 in craniofacial development was initially identified through our recessive ENU-based forward genetic screen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations